Efficacy of intravenous dexamethasone for post-operative pain relief in elective cesarean section - Swetha Purohit; Kavi, Chandrashekarappa; Shobha MM (Asian Journal of Medical Sciences, 2023)
Background: Various additives have been evaluated for the purpose of enhancing quality of analgesia and prolonging duration of spinal anesthesia. Aims and Objectives: This randomized study was conducted to evaluate the efficacy of intravenous dexamethasone in spinal anesthesia. Materials and Methods: A total of 100 patients scheduled for lower segment cesarean section under spinal anesthesia were randomly allocated into two groups, Group-1 and Group-2, including 50 patients each. All the patients received injection bupivacaine 0.5% heavy 10 mg for spinal anesthesia. Group-1 received injection dexamethasone 8 mg intravenously, and Group-2 received injection normal saline 2 cc immediately after spinal anesthesia. Duration of sensory and motor block, post-operative analgesia, visual analog pain scale (VAS) score, time of rescue analgesia, total analgesic requirement in the first 24 h, intra- and post-operative hemodynamics, and side effects if any were recorded. Results: The mean duration of sensory block (min) in Group-1 and Group-2 was 162.50 and 106.17, respectively. Time to the requirement of first rescue analgesia was 8.67 h in Group-1 and 4.40 h in Group-2. Significant changes seen in VAS score in post-operative period after 1 h of surgery in Group-1 and Group-2. Group-1 had more duration of sensory block, prolonged requirement of first rescue analgesia. Duration of motor block and intra- and post-operative hemodynamic parameters was comparable in both the groups. No side effects were recorded in both the groups. Conclusion: We conclude that administration of dexamethasone 8 mg intravenously prolongs the duration of post-operative analgesia and sensory block in patients undergoing lower segment cesarean section under spinal anesthesia.